Proyeksi Indeks Pembangunan Berwawasan Kependudukan (IPBK) Menggunakan Single Dan Double Exponential Smoothing (Studi Di Kabupaten Gorontalo 2024 – 2026) - Akolo, Ingka Rizkyani; Umar, Razak; Yasin, Indri Afriani (Jambura Journal of Probability and Statistics, 2024)
The Population-Oriented Development Index (IPBK) is an important indicator for measuring regional development success, focusing on human resource quality. This study aims to project the IPBK for 2024–2026 and identify the best method for projecting the IPBK in Gorontalo Regency. The projection methods used are single and double exponential smoothing. The IPBK data for Gorontalo Regency was obtained from the 2024 BKKBN Central Publication. The variables include participation (X1), sustainability (X2), inclusiveness (X3), holistic integration (X4), equality (X5), and IPBK (X6). The data was analyzed using Minitab 16 software. The results indicate that the double exponential smoothing method outperforms the single exponential smoothing method for projecting the IPBK and its dimensions in Gorontalo Regency, achieving a MAPE value of less than 10%. The IPBK projections and its dimensions for 2024–2026 using the double exponential smoothing method show an annual upward trend, predicting that by 2025–2026, Gorontalo Regency's IPBK status will rise from category 3 (upper-middle status) to category 4 (high status). This high status indicates that Gorontalo Regency has achieved significant progress in key indicators reflecting the welfare and quality of life of its residents.